The Influence of Teacher Learning Quality on Student Achievement and Character at SMP Negeri 2 Lhoong: A Literature Review - sittinurbani ubbg; rahmattullah; Siti Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to explore the impact of the quality of teaching provided by teachers on student achievement and character development at SMP Negeri 2 Lhoong. The quality of teaching is a key factor in the education system that can influence academic outcomes as well as the character formation of students. In this context, the quality of teaching encompasses various aspects, such as teaching skills, utilized methods, the interaction between teachers and students, and the assessments applied during the learning process. The methodology employed in this study is a literature review, which involves analyzing various relevant literature and sources. This research examines the educational theories underlying effective teaching practices and investigates previous studies that indicate a positive relationship between teaching quality and student academic performance. Various studies also show that engaging and interactive teaching quality can motivate students to learn better, which directly contributes to their academic achievements. The findings of this study demonstrate that high-quality teaching, characterized by varied instructional methods, the use of technology in the classroom, and constructive feedback from teachers, can significantly enhance student learning outcomes. Furthermore, quality teaching plays an essential role in the character development of students, teaching them values such as discipline, cooperation, and responsibility. This research emphasizes that education should not focus solely on cognitive aspects but also on character development as an integral part of the learning process.